The Effectiveness of a Weak Opioid Medication versus a Cyclo-Oxygenase-2 (COX-2) Selective Non-Steroidal Anti-Inflammatory Drug in Treating Flare-Up of Chronic Low-Back Pain: Results from Two Randomized, Double-Blind, 6-Week Studies - O'Donnell, JB; Ekman, EF; Spalding, WM; Bhadra, P; McCabe, D; Berger, MF (Journal of international medical research, 2009)
Two 6-week studies compared the analgesic efficacy, tolerability and safety of a non-steroidal anti-inflammatory drug (celecoxib 200 mg twice a day [bid]) and an opioid (tramadol HCl 50 mg four times a day [qid]) in subjects with chronic low-back pain (CLBP). Successful responders (primary endpoint) were defined as subjects completing 6 weeks of treatment and having ≥ 30% improvement on the Numerical Rating Scale for pain. A total of 796 and 802 subjects were randomized to treatment in study 1 and study 2, respectively. A significantly greater percentage of celecoxib-treated subjects were successful responders compared with tramadol HCl-treated subjects (study 1: 63.2% versus 49.9%, respectively; study 2: 64.1% versus 55.1%, respectively). Fewer adverse events (AEs) and serious AEs were reported in the celecoxib-treated group. Overall, celecoxib 200 mg bid was more effective than tramadol HCl 50 mg qid in the treatment of CLBP, with fewer AEs reported.